Community Empowerment through the Bestari Waste Bank Program in Sidoarjo Regency: Pemberdayaan Masyarakat melalui Program Bank Sampah Bestari di Kabupaten Sidoarjo - Marta, Silvy; Usrotin, Ilmi (Indonesian Journal of Public Policy Review, 2022)
The purpose of this study was to describe and analyze community empowerment through the Bestari Waste Bank program in Lebo Village, Sidoarjo District, Sidoarjo Regency. This research method uses qualitative, data collection is done by in-depth interviews, observation and review of relevant literature. The technique of determining the informants used purposive sampling. The informants of this research include the Head of Lebo Village, Sidoarjo District, Chair of the Lebo Village Bestari Garbage Bank, Lebo Village Secretary and members or customers of the Lebo Village Bestari Garbage Bank. The data analysis technique in this study is a qualitative analysis type (referring to the theory of Miles and Huberman. The results show that Community Empowerment through the Bestari Waste Bank Program in Lebo Village, Sidoarjo District, Sidoarjo Regency) seen from human development, including: increasing public knowledge on the knowledge aspect carried out by way of socialization related to waste sorting, on the aspect of attitude by fostering an entrepreneurial, professional and independent attitude and on the skill aspect by providing training to create recycled waste so that it can increase the economic value of increasing the Bargaining Position of the Community by synergizing with various parties, ranging from bureaucracy, academics, community leaders and business actors. Obstacles in community empowerment through the Bestari Waste Bank program in Lebo Village, Sidoarjo District, Sidoarjo Regency, among others, lack of public understanding regarding waste sorting, low community participation in waste management, lack of community skills in waste management